How Well Does the Internet Answer Patients' Questions about Inflammatory Bowel Disease?. (2010) - Promislow, Steven; Walker, John R; Taheri, Mohammad; Bernstein, Charles N
Abstract : BACKGROUND: The Internet is an increasingly important source of health information. OBJECTIVE: To assess how well common websites answered patients' questions regarding inflammatory bowel disease (IBD). METHODS: Thirty websites were identified and evaluated. Based on a previous survey of patient information needs, a comprehensive question list was developed in the three following areas: medical information (seven items), medical treatment (six items) and self-management (eight items). The websites were evaluated for the amount of information they provided to answer each question using two standard measures of information quality – the DISCERN and the Ensuring Quality Information for Patients scales. RESULTS: Four particularly strong websites, scoring highest (on a scale from 1 to 5) in terms of IBD information, were the Crohn's and Colitis Foundation of America (mean information score 4.3), About.com (4.2), HealthCentral (3.8) and WebMD (3.8). These websites also scored well on the DISCERN and the Ensuring Quality Information for Patients quality scales. Most websites provided at least adequate information on common symptoms, complications, treatments and what is known (or not known) about the causes of IBD. However, many web-sites did not provide adequate information about prognosis, possible side effects of treatment and risks of developing cancer. Information regarding self-management was covered to a very limited extent. CONCLUSION: Websites could be strengthened by providing more of the information patients deem to be important, and by more clearly identifying sources of information and the date the information was updated. Most websites would benefit from more attention given to reducing the reading level and improving the organization of material.